Precarity and Why Indie Game Developers Can't Save Us from Racism. (December 2019) - Srauy, Sam
Exploring issues of labor and inequality at the intersection of AAA and indie sectors, this article interrogates the perception of the indie sector as key to mitigating the production of racializing or racist game content. As developers are central to the industry and the larger games culture, their views reveal how indies are imagined as a privileged site free from economic pressures where racism can be ameliorated. Based on interviews with developers, I argue that the project to redress representational inequities within games is shifted on to indie developers, intensifying their emotional and cultural labor. Indie game developers are imagined as the solution, yet this perspective underestimates the precariousness of independent game production. Economic precariousness may encourage indies to repeat certain patterns of racial representation.